2013
DOI: 10.3390/ma6041452
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration Process of Hofmann-Type Layered Solids

Abstract: In the present work the dehydration process of layered solids with formula unit M(H2O)2[Ni(CN)4]·nH2O, M = Ni, Co, Mn; n = 1, 2, 4 is studied using modulated thermogravimetry. The results show that water molecules need to overcome an energetic barrier (activation energy between 63 and 500 kJ/mol) in order to diffuse through the interlayer region. The related kinetic parameters show a dependence on the water partial pressure. On the other hand, X-ray diffraction results provide evidence that the dehydration pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…48 Noticeably, the amount of water molecules in such systems remains a complex problem since it influences the crystal structure (three different phases are known). [42][43][44] However it could be noticed that the non-functionalized material 1 shows a step at about a higher 1.8 H2O per unit, in accordance with the two expected CUS in trans position of the octahedral Ni 2+ ions. All these data clearly indicate that despite the PSM, the functionalized clathrates could efficiently adsorb different species in line with the obtained porous volumes based on nitrogen sorption isotherms (Fig.…”
Section: Adsorption Studiessupporting
confidence: 61%
See 2 more Smart Citations
“…48 Noticeably, the amount of water molecules in such systems remains a complex problem since it influences the crystal structure (three different phases are known). [42][43][44] However it could be noticed that the non-functionalized material 1 shows a step at about a higher 1.8 H2O per unit, in accordance with the two expected CUS in trans position of the octahedral Ni 2+ ions. All these data clearly indicate that despite the PSM, the functionalized clathrates could efficiently adsorb different species in line with the obtained porous volumes based on nitrogen sorption isotherms (Fig.…”
Section: Adsorption Studiessupporting
confidence: 61%
“…1). [42][43][44] The water molecules occupying the axial coordination sites could be easily removed to generate CUS. [39][40][41] Thus, activation of 1 under vacuum at 130 °C followed by the addition of 2 equivalents of either R, S, or racemic (+/) phenylethylamine (L, Scheme 1) in chloroform affords the formation of light purple solids for R-1, S-1 and light blue solid for (+/)-1, respectively (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, no line broadening was observed in the Raman spectra . Presumably, the observed change in SCO behavior results both from the observed particle size reduction in the thin film,[29a] and the interaction at the substrate‐film interface as recently reported by Delgado et al An excessive laser irradiation energy would result in a complete removal of structural water and/or pyrazine molecules, which can even lead to the framework collapse . Both effects can however be excluded, since the first one would not lead to a positive pressure effect, as observed by Bonhommeau et al, whereas the second one would lead to a network alteration, which has not been confirmed by X‐ray diffraction (Figure ).…”
Section: Resultsmentioning
confidence: 71%
“…According to the FT-IR spectrum, the product exhibits a strong peak at 2193 cm 2¹ have been reported. 23,24 One is a sphalerite-type three-dimensional compound and the other is a Hoffman-type two-dimensional layer compound. XRD pattern of S1 is quite different from the calculated pattern using CIF file of sphaleritetype materials ( Figure S4).…”
mentioning
confidence: 99%